FRI0163 ANTIPHOSPHOLIPID PATTERNS PREDICT THE RISK OF THROMBOSIS IN SYSTEMIC LUPUS ERYTHEMATOSUS. (2nd June 2020) - Demir, S.; LI, J.; Magder, L.; Petri, M. A.
Abstract : Background: It is well known that Lupus anticoagulant (LAC) positivity is more strongly associated with both arterial and venous thrombosis than either anticardiolipin (aCL) or anti-β2glycoprotein (aB2GPI) antibodies (1). An unanswered question is the contribution of which combinations of positive aPLs to thrombosis risk. Objectives: We aimed to evaluate which aPL combinations increase the risk of future thrombosis in patients with Systemic Lupus Erythematosus (SLE). Methods: This prospective analysis included SLE patients who had been tested for all 3 aPLs in Hopkins Lupus Cohort. We constructed a dataset with one record per month of follow up for each patient. Rates of thrombosis for each aPL or each combination of aPL were calculated as the number of thromboses divided by the number of person months at risk and the results are converted to rates per 1000 person-years. Results: There were 805 patients with a complete profile of 7 aPLs with a total of 73417 person months of follow up. LAC was the most predictive of any [3.47 (1.96, 6.14) p<0.0001], venous [4.3 (1.99, 9.25) p=0.0002], and arterial [3.37 (1.51, 7.53) p= 0.0029] thrombosis. In individual models, aB2GPI positivity was a significant risk factor for any [1.90 (1.16, 3.13) p=0.0113] and venous [2.3(1.23, 4.61) p=0.0103] thrombosis. When we looked at patients who were LAC positive, and asked if having another positive aPL increase the risk ratio for any/venous/arterial thrombosis, we found that having aB2GPI IgA appeared to add significant risk to any [1.68 (1.01, 2.79) p=0.044], and venous [2.01 (1.02, 3.97) p=0.043] thrombosis among those with or without LAC (Table 1 ). Conclusion: Our study shows that LAC is still the best predictor of risk of any, arterial and venous thrombosis in SLE. Moreover, aB2GPI IgA positivity appeared to add also a significant risk to any and venous thrombosis. Therefore, the clinical significance of IgA anti-β2GPI deserves further investigation in SLE patients. References: [1]Galli M, Luciani D, Bertolini G, Barbui T. Lupus anticoagulants are stronger risk factors for thrombosis than anticardiolipin antibodies in the antiphospholipid syndrome: a systematic review of the literature. Blood. 2003;101(5):1827-32. Acknowledgments: The Hopkins Lupus Cohort was funded by NIH grant number RO1 AR069572. Disclosure of Interests: Selcan Demir: None declared, Jessica Li: None declared, Laurence Magder: None declared, Michelle A Petri Grant/research support from: GSK, Eli Lilly and Company, Consultant of: Eli Lilly and Company